Presentation is loading. Please wait.

Presentation is loading. Please wait.

Solving Systems using Substitution

Similar presentations


Presentation on theme: "Solving Systems using Substitution"β€” Presentation transcript:

1 Solving Systems using Substitution

2 Substitution – Replacing Evaluate one equation for one variable
Example: 𝑦=3π‘₯+7 Substitute the resulting expression for the variable in the second equation.

3 Steps to Solving a Sd Kf

4

5 Solve the system by using substitution: y = 4x – 1 2x + 2y = 3
Because y = 4x – 1, substitute 4x – 1 for y in 2x + 2y = 3. 2x + 2y = 3 οƒŸ Write the second equation 2x + 2(4x – 1) = 3 οƒŸ Substitute 4x – 1 for y 2x + 8x – 2 = 3 οƒŸ Use the Distributive Property 10x – 2 = 3 οƒŸ Simplify 10x = 5 οƒŸ Add 2 to each side x = Β½ οƒŸ Divide each side by 10 Substitute Β½ for x in either equation and solve for y. y = 4x – 1 y = 4(Β½) – 1 y = 2 – 1 y = 1 The solution of the system is (Β½, 1)

6 Solve the system by using substitution: -9x + 5y = -1 -3x + y = 4
The solution of the system is (-3.5, -6.5)

7 Solve the system by using substitution: -2x + y = 3 3x – 2y = 0
The solution of the system is (-6, -9)

8

9

10

11


Download ppt "Solving Systems using Substitution"

Similar presentations


Ads by Google